LANDASAN TEORITIS DAN TEKNIK SUPERVISI DALAM MENINGKATKAN PEMBELAJARAN - Damayanti, Husnaya Dwi; Ahmad Danial Akyas; Mia Nurussafaah; Restu Agung Santoso; Mardiyah, Mardiyah (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2025)
Educational supervision is one of the essential instruments for improving the quality of learning in schools. This study aims to describe the theoretical foundations and supervision techniques in enhancing learning quality. The research method employed is library research through an analysis of various literatures, books, scientific articles, and regulations relevant to educational supervision. The findings indicate that educational supervision has evolved from merely administrative control to academic guidance that is more humanistic in nature. The implementation of supervision includes individual, group, and case-based approaches, each providing different strategies for improving learning quality. In addition, scientific, artistic, and clinical approaches to supervision offer systematic, flexible, and contextual frameworks that align with the needs of teachers and students. These findings emphasize that professionally conducted supervision plays a significant role in creating innovative, effective, and sustainable learning processes.